TINJAUAN KEKERASAN DAN PSIKOLOGIS PADA NOVEL TEMBANG ILALANG KARYA MD AMINUDIN - Sarwidi Sarwidi; Titi Wahyukti (Khazanah Pendidikan, 2013)
This article presented the depiction of psychological and physical violence by communists and Dutch colonies which were found in the novel of Tembang Ilalang. Such a physical violence happened to the main characters (protagonists) in terms of political force in the forms of striking, kicking, torturing, imprisoning, even the threat of killing. At the same time, the psychological violence was also appearing with the case that some people (the antagonists) had given harsh words and verbal abuse directed at Asroel as the protagonist in terms of having different ideology. Beside that his family and relatives were also sentenced to prison with some torturous experience, such a psychological violence made him suffer mentally a lot. According to Galtung’s point of view, those kinds of violence can be classified into direct violence and indirect one. The person who got direct violence would directly suffer from physical and mental violence as the result of ill treatment given to him, whereas indirect violence would effect the person indirectly with the feeling of sadness, loneliness and mournfulness as the result of ill treatment given to his family or relatives. Such a bad and sad experience during Asroel’s struggle for nation’s freedom can also be found in the real life of our community.